087 Incremental value of high-resolution cardiovascular magnetic resonance myocardial perfusion imaging in suspected coronary artery disease. (16th May 2012) - Motwani, M; Maredia, N; Fairbairn, T A; Kozerke, S; Radjenovic, A; Greenwood, J P; Plein, S
Abstract : Introduction: Although accelerated high-spatial-resolution cardiovascular magnetic resonance (CMR) perfusion imaging has recently been shown to be clinically feasible, there has not yet been a direct comparison with standard-resolution methods. We hypothesised that higher spatial resolution detects more subendocardial ischaemia and leads to greater diagnostic accuracy for the detection of angiographically defined CAD. This study compared the diagnostic accuracy of high-resolution and standard-resolution CMR perfusion imaging in patients with suspected coronary artery disease (CAD). Methods: A total of 111 patients with suspected CAD were prospectively recruited. All patients underwent two separate perfusion CMR studies on a 1.5 Tesla CMR scanner (Intera CV, Philips Healthcare, Best, the Netherlands), one with standard-resolution (2.5×2.5 mm in-plane resolution) and one with high-resolution (1.6×1.6 mm in-plane resolution) acquisition. High-resolution acquisition was facilitated by eightfold k-t broad linear speed up technique (BLAST) acceleration. Two observers visually graded perfusion in each myocardial segment on a 4-point scale. Segmental scores were summed to produce a perfusion score for each patient. All patients underwent invasive coronary angiography. Significant CAD was defined as a coronary artery stenosis of ≥50% diameter on quantitative coronary angiography. Results: CMR data were successfully obtained in 100 patients. A typical example is shown in Abstract 087 figure 1 . In patients with CAD (n=70), more segments were determined to have subendocardial ischaemia with high-resolution acquisition than with standard-resolution acquisition (279 vs 108; p<0.001). High-resolution acquisition had a greater diagnostic accuracy than standard-resolution acquisition for identifying single-vessel disease (area under the curve [AUC]: 0.88 vs 0.73; p<0.001) or multi-vessel disease (AUC: 0.98 vs 0.91; p=0.002) and overall (AUC: 0.93 vs 0.83; p<0.001) (Abstract 087 figure 2 ). Conclusions: Our study shows that high-resolution CMR perfusion imaging has greater diagnostic accuracy than standard-resolution acquisition for the detection of CAD in both single and multi-vessel disease patients and detects more subendocardial ischaemia.